The use of cone beam imaging to determine cochlear implant electrode position in human temporal bones. (November 2013) - Saeed, Shakeel R; Selvadurai, David; Beale, Tim; Murray, Brendan; Boyd, Paul; Biggs, Nigel; Gibson, Peter; Risi, Frank
<x content-type="archive" xml:space="preserve">Abstract</x> This paper describes the outcomes of cochlear implantation in eight cadaveric temporal bones using cone-beam CT imaging and histological examination with respect to scalar position of the electrode array.